Pengaruh Model PBL Bermedia Muatan Lokal dan Gaya Belajar terhadap Hasil Belajar Siswa pada Materi Klasifikasi Zat di Kelas VII SMP - Fitri Karlina; Rayandra Asyhar; Asrial Asrial (Universitas Jambi, 2014)
Local content mediated PBL model is a facility to make students active and also as a media to deliver massages in learning process that make an independent student. By knowing student’s learning style, the teacher can implement the suitable learning model. So it can increase the learning result. Based on the result of this research we found the effect of learning model of local content mediated PBL to the learning result. The learning result is different between students who have kinesthetic learning style and student who have auditory learning style. Given the existence interaction between learning models of local content mediated PBL and learning style to the student’s learning result it can be concluded that by knowing student’s learning style, the teacher can implement the appropriate lesson model that ultimately could increase students’ learning result.